2019
DOI: 10.3390/molecules24203710
|View full text |Cite
|
Sign up to set email alerts
|

Black Chokeberry Aronia Melanocarpa L.—A Qualitative Composition, Phenolic Profile and Antioxidant Potential

Abstract: Black chokeberry (Aronia melnocarpa) is a source of many bioactive compounds with a wide spectrum of health-promoting properties. Fresh, unprocessed chokeberry fruits are rarely consumed due to their astringent taste, but they are used in the food industry for the production of juices, nectars, syrups, jams, preserves, wines, tinctures, fruit desserts, jellies, fruit teas and dietary supplements. Polyphenols are biofactors that determine the high bioactivity of chokeberries, some of the richest sources of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(147 citation statements)
references
References 101 publications
12
133
0
2
Order By: Relevance
“…Crucial for the formation of chlorophyll are micro-and macroelements such as K, Mg, Fe and Cu which are present in plant extracts [27]. As it was shown in the work of Sekeroglu et al [80], hypericum can serve as a source of B, Cu, Fe, Mg, Mn, Mo, and Zn, whereas chokeberry of the following minerals: Na, K, Ca, Mg, Fe, Zn, and I [35,37]. Furthermore, carotenoids which are essential in photosynthesis act also as free radical scavengers and protect chlorophyll from photo-oxidative destruction [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucial for the formation of chlorophyll are micro-and macroelements such as K, Mg, Fe and Cu which are present in plant extracts [27]. As it was shown in the work of Sekeroglu et al [80], hypericum can serve as a source of B, Cu, Fe, Mg, Mn, Mo, and Zn, whereas chokeberry of the following minerals: Na, K, Ca, Mg, Fe, Zn, and I [35,37]. Furthermore, carotenoids which are essential in photosynthesis act also as free radical scavengers and protect chlorophyll from photo-oxidative destruction [27].…”
Section: Discussionmentioning
confidence: 99%
“…Aloe Aloe vera L. Burm. f. Vitamins (A, C, E, B1, B2, B6, B9, B12), choline, enzymes (aliiase, alkaline phosphate, amylase, bradykinase, carboxypeptidase, catalase, cellulose, lipase, peroxidase), minerals (Ca, Cr, Cu, Se, Mg, Mn, K, Na, Zn, Fe, P), sugars: monosaccharides (glucose, fructose), polysaccharides (glucomannans/polymannose), anthraquinones (aloin, emodin), fatty acids (cholesterol, campesterol, β-sisosterol, lupeol), hormones (auxins, gibberellins), amino acids (A, R, D, E, G, H, I, L, K, M, F, P, T, Y, V), proteins (lectins), salicylic acid, lignin, saponins, carbohydrates (pure mannan, acetylated mannan, cellulose, pectic substance, xylan) [32][33][34] Aronia Aronia melanocarpa (Michx) Elliott Carbohydrate (glucose, fructose, sucrose, sorbitol), dietary fibre (pectins), fat, proteins, organic acids (l-malic acid, citric acid, isocitric acid, tartaric acid, quinic acid, succinic acid, fumaric acid), vitamins (C, B1, B2, B3, B5, B6, B9, E, K), minerals (Na, K, Ca, Mg, Fe, Zn, I), phytochemicals (carotenoids: β-carotene, β-cryptoxanthin; phenols; amygdalin), nitrate, nitrite [35][36][37] Red beet Beta vulgaris L. subs. vulgaris Nitrate, phenolics (flavonoids, phenolic acids, phenolic amides), vitamins (A, B), carotenoids, betalains (betacyanins: betanin, isobetanin; betaxanthins: vulgaxanthin I, vulgaxanthin II, indicaxanthin), minerals (Mg, Na, K, P, Ca), sugars, proteins, fibre [38][39][40] Horsetail Equisetum arvense L.…”
Section: Active Compounds Referencesmentioning
confidence: 99%
“…Thus, the chlorogenic acid content showed a similar pattern to the catechol content. Sidor and Gramza-Michałowska [26] reported that Chokeberries mostly contain chlorogenic and neochlorogenic acids. Other phenolic acids are cryptochlorogenic acid, p-coumaric acid and its derivatives, caffeic acid and its derivatives, protocatechuic, vanillic, ferulic, salicylic, syringic, 4-hydroxybenzoic and ellagic acids.…”
Section: Polyphenol Contentmentioning
confidence: 99%
“…According to the producer's declaration, the extract also contained sugar, sugar alcohols (sorbitol, parasorboside), triterpenes, phytosterols, carotenoids, minerals, and vitamins. Moreover, vitamins from group B (B 1 , B 2 , B 3 , B 5 , and B 6 ), vitamins C, E, and K, β-carotene, β-cryptoxanthin, violaxanthin, dietary fiber, tannins, organic acids (l-malic acid, citric acid), carbohydrates, proteins, as well as calcium, magnesium, and iron [1,9] are present in chokeberries. The concentration of Cd in the 0.1% AE was <0.05 µg/L [10].…”
Section: Ingredients Of Aementioning
confidence: 99%
“…It seems reasonable that, among plants abundant in polyphenols, special attention should be paid to Aronia melanocarpa L. (Rosaceae), the berries of which (chokeberries) are one of the richest sources of these compounds [1,2,4,9]. Chokeberries have proven beneficial impact on health and thus they are widely recommended as functional food [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%